Hubungan Pelatih Terhadap Kreativitas Siswa Dalam Pengembangan Diri Seni Tari Di SMP Pembangunan Laboratorium Unp - Reza Trinanda; Indrayuda Indrayuda (SENDRATASIK UNP, 2019)
This article aims to find out and describe the trainer's relationship to the students ' creativity in the development of dance art in junior high School of UNP. This type of research is a descriptive study that produces Qualitative data. The main instrument in this research is its own researchers. Data collection techniques are conducted by way of library studies, observation and documentation. The stage for analyzing data is to reduce data, data presentation and withdrawal of conclusions. The results showed that the activities of self-development in SMP UNP Laboratory development do not have a regular trainer and have different strategies and methods. The impact is that students lack the ability to develop patterns of motion, students feel corner and not confident if unable to mimic the techniques taught by the trainer, as well as students do not freely explore and express themselves. Therefore, the idea arises to see how the technique, and expression of the students in the dance of the Pasambahan, which has been given by his trainer.